กระบวนการแนวคิดพื้นฐานทางปรัชญา - ปิยสีโล, อดิศักดิ์ (วารสารบัณฑิตศาส์น มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
กระบวนการแนวคิดพื้นฐานทางปรัชญา PROCESS OF BASIC PHILOSOPHICAL CONCEPTS บทคัดย่อ บทความวิชาการนี้ มีวัตถุประสงค์ 1) เพื่อศึกษาความหมายและขอบเขตของปรัชญา 2) เพื่อศึกษาความสำคัญและลักษณะะของปรัชญา 3) เพื่อศึกษาพัฒนาการของปรัชญาตะวันออกและปรัชญาตะวันตก ซึ่งบทความนี้เรียบเรียงจากการศึกษาเอกสาร แนวคิด ทฤษฎี และงานที่เกี่ยวข้องทั้งนี้ปรัชญาเป็นศาสตร์ที่เน้นศึกษาถึงพัฒนาการทางด้านความคิดของมนุษย์ ดังนั้นลักษณะโดยทั่วไปของปรัชญาจึงมุ่งเน้นที่จะคิดค้นวิธีคิด กระบวนทัศน์ โลกทัศน์ ชีวทัศน์ ของมนุษย์ในแต่ละยุคสมัย มนุษย์ที่เกิดมาในบริบทเดียวกัน ให้คำตอบ มีการมองโลกและชีวิตต่างกัน และเมื่อให้เสนอรูปแบบในการจัดการชีวิตย่อมต่างกันไปทางความคิดเห็นของแต่ละบุคคล ปรัชญาทำหน้าที่นำเอากระบวนการทางความคิดทั้งหมดนั้นมาจัดเข้าเป็นระบบใหญ่ ดังนั้นเมื่อเรามองว่าพัฒนาการของโลก แต่ละช่วงจะพบพัฒนาการหลายด้าน ปรัชญาสนใจในประเด็นพัฒนาการด้านความคิดของมนุษย์ นี้เป็นลักษณะของปรัชญา โดยมีขอบข่ายให้ศึกษาความหมายและขอบเขตของปรัชญา สาขาปรัชญาและสาระสำคัญของปรัชญาสาขาต่างๆ และศึกษาพัฒนาการของปรัชญาตะวันออกและปรัชญาตะวันตก พอเข้าใจแนวความคิดและทฤษฎีต่างๆ ของนักปรัชญา ลักษณะสำคัญ ของบทความวิชาการนี้มุ่งเน้นการให้ความรู้พื้นฐานทางด้านปรัชญา ทฤษฎีแนวคิด กระตุ้นให้คิด โดยมีเนื้อหาสาระหลักใหญ่ๆสำคัญ 5 ประการคือ อภิปรัชญา ญาณวิทยา จริยศาสตร์ สุนทรียศาสตร์ และตรรกศาสตร์ Abstract This article has 3 objectives: 1) To study the meaning and scope of philosophy, 2) the magnificence and nature of philosophy, and 3) both development of East philosophy and West philosophy. This compiled study employs the document, concepts, theories, and other related studies Because philosophy is the science emphasizing the study of human thought’s development the nature generally focuses on discovering the think – method, paradigm, world view, and life view in each of periods. Though the people born in the same circumstance, but they are different in replies, and opinions towards the world and life. Their suggested models to manage life are also different on their opinions. Philosophy collects all the thinking processes and sets up a macro system. When we examine the development of the world, we find out the development in many aspects in each period. Philosophy is interested in the topic of human thought’s development – the nature of Philosophy. Its boundary covers the study meaning and scope of Philosophy, Philosophy’s branches and the essential text of that branches, and also both of East philosophy & West philosophy development so as to understand philosopher’s concepts and theories. This article’s essesce is written to pave the way for basic knowledge of philosophy, theories, concepts, and brian-tickling. The study is devided into 5 main parts comprising of Meta - philosophy Epistemology, Ethics, esthetics, and Logic.